2013
DOI: 10.1111/jph.12182
|View full text |Cite
|
Sign up to set email alerts
|

Variants of Hop stunt viroid Associated with Mulberry Vein Clearing in Iran

Abstract: Samples of mulberry leaves showing vein clearing, yellow speckle and leaf deformation symptoms were collected in the Fars Province of Iran. Grafting of buds from affected trees onto a number of healthy mulberry rootstocks resulted in transmission of the pathogen 40 days postinoculation. Likewise, mechanical inoculation of sap from affected leaves resulted in induction of similar symptoms in mulberry seedlings. Total nucleic acid was extracted from leaf tissues and subjected to reverse transcription polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The sequence data con rmed the HSVd association with mulberry with the high percentage homology with HSVd-grapevine, isolated from Russia, China, Indian (Sahana et al 2013;Singhal et al 2019), and widely around the world. The phylogenetic analysis of the HSVd Indian mulberry isolates showed an evolutionary relationship with those from grapevine, plum, peach, apple and hop reported from various countries including India; i.e.,"grapevine"or "grapevine-hop" group (Amari et al 2001;Sano et al 2001).Which was somewhat different from those reported from Italy-Lebanon, Iran, and China, wherein mulberry isolates clustered together with those of "citrus" group, "plum" group, and "hop" group, respectively (Elbeaino et al 2012;Amiri Mazhar et al 2014;Lu et al 2023). These results indicate that the HSVd mulberry isolates reported so far from Italy-Lebanon, Iran, China, and now from India belong to distinct groups depending on the region, and do not shows host speci city.…”
Section: Sequencing and Phylogenetic Analysiscontrasting
confidence: 56%
See 2 more Smart Citations
“…The sequence data con rmed the HSVd association with mulberry with the high percentage homology with HSVd-grapevine, isolated from Russia, China, Indian (Sahana et al 2013;Singhal et al 2019), and widely around the world. The phylogenetic analysis of the HSVd Indian mulberry isolates showed an evolutionary relationship with those from grapevine, plum, peach, apple and hop reported from various countries including India; i.e.,"grapevine"or "grapevine-hop" group (Amari et al 2001;Sano et al 2001).Which was somewhat different from those reported from Italy-Lebanon, Iran, and China, wherein mulberry isolates clustered together with those of "citrus" group, "plum" group, and "hop" group, respectively (Elbeaino et al 2012;Amiri Mazhar et al 2014;Lu et al 2023). These results indicate that the HSVd mulberry isolates reported so far from Italy-Lebanon, Iran, China, and now from India belong to distinct groups depending on the region, and do not shows host speci city.…”
Section: Sequencing and Phylogenetic Analysiscontrasting
confidence: 56%
“…Amiri Mazhar et al (2014) speci cally detected HSVd from mulberry trees exhibiting vein-clearing and yellow speckle symptoms, and showed that the mulberry disease in question is transmitted from mulberry to mulberry by grafting the buds of the diseased tree onto the mulberry seedlings and by mechanical inoculation of the mulberry seedlings with the sap (but not puri ed preparation) from the diseased leaves. Since HSVd was detected again from inoculated seedlings, they concluded that vein clearing and deformation of mulberry leaves is a transmissible disease associated with HSVd.…”
Section: Sequencing and Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Hop stunt viroid has previously been reported earlier as the agent of citrus cachexia in northern areas of Iran (Mazandaran Province) (Bové, ). Although it has not been clearly demonstrated, some of Iranian HSVd variants have been reported to be associated with the yellow corky vein disease of sweet orange, split bark of sweet lime, and mulberry vein clearing and leaf deformation symptoms (Amiri‐Mazhar, Bagherian, & Izadpanah, ; Amiri‐Mazhar, Bagherian, Salahi‐Ardakani, & Izadpanah, ; Bagherian & Izadpanah, ). Pistachio was reported as a new natural host of HSVd from Tunisia by Elleuch et al (), and pistachio ampelovirus A (PAVA) and citrus bark cracking viroid‐pistachio (CBCVd‐pis) have been recently identified as two other new viral and viroid agents (Al Rwahnih et al, ).…”
Section: Introductionmentioning
confidence: 99%